Ubiquitous plasticizer, Di-(2-ethylhexyl) phthalate enhances existing inflammatory profile in monocytes of children with autism - Nadeem, Ahmed; Ahmad, Sheikh F.; Al-Harbi, Naif O.; AL-Ayadhi, Laila Y.; Attia, Sabry M.; Alasmari, Abdullah F; As Sobeai, Homood M; Bakheet, Saleh A. (Toxicology (Amsterdam), 2020)
[Display omitted] •DEHP upregulates NFkB/STAT3 expression in monocytes of ASD children.•DEHP upregulates IL-6, TNF-α, IL-1β in monocytes of ASD children.•Inhibition of NFkB and STAT3 attenuates DEHP-induced inflammation in monocytes of ASD. Genetic as well as environmental factors are believed to play a significant role in the pathogenesis and progression of autism spectrum disorder (ASD). Phthalates are ubiquitous environmental contaminants as they are used plasticizers in several household/industrial products such as vinyl flooring, plastic toys, and cosmetic products. One of the plasticizers that is quite prevalent in these products is di-2-ethylhexyl phthalate (DEHP) which can cause human exposure via dermal/inhalation/ingestion routes. DEHP and its metabolites are associated with behavioral dysregulations and reported to be increased in systemic circulation of ASD children. DEHP is reported to cause upregulation of several inflammatory cytokines in different cells/tissues, however its role in inflammatory signaling of ASD monocytes has not been investigated earlier. Therefore, this study evaluated the effects of DEHP (at 5 μM final concentration for 24 h) on inflammatory profile (NFkB, STAT3, IL-6, TNF-α, IL-1β) in monocytes of ASD subjects and typically developing control (TDC) children. Our data show that DEHP upregulates NFkB/STAT3 expression which is associated with increased inflammatory profile in monocytes of ASD and TDC subjects, however its effect is much greater in magnitude in the former group. This was confirmed by utilization of NFkB inhibitor, PDTC and STAT3 inhibitor, Stattic which caused reduction in inflammatory cytokines from DEHP-treated monocytes in ASD group. In short, DEHP causes further elevation in inflammatory signaling in ASD monocytes which could be due to existing inflammation in this group. These data suggest that use of plasticizers such as DEHP should be minimized in order to avoid their potential effects on immune dysfunction associated with ASD.